Electrocoagulation using novel configurations electrodes for treatment of textile wastewater - Naje, Ahmed Samir (2016)
Textile wastewater is considered as one of the most polluted wastewater. Conventional chemical coagulation is the most famous technique used to treat the textile effluent. However, this method produces low removal rate, long retention time and a large quantity of sludge and chemicals. The electrocoagulation (EC) technology is an active wastewater treatment used before sedimentation and filtration. It is still in the "black box" stage where process design, control, and optimization have been primarily empirical. In this research, the EC process was performed in two models for the treatment of textile wastewater. The first model is the conventional reactor with a new configuration that has static electrodes, classified in two phases. The two phases are the EC process alone, using Mp Al-Bp Al or Mp Al-Bp Fe and EC combined with electrooxidation process (EO) in the same reactor using MpTi-Bp Al or MpTi-Bp Fe. The second model is a novel reactor design with a rotating anode using aluminum electrodes. The rotating anode consists of 10 impellers supported by a shaft with 10 rings used as a cathode. The operational parameters were investigated, and the process was performed under optimal conditions. For model one, the results showed that the Mp Al-Bp Al was more effective than the Mp Al-Bp Fe and it was more efficient than chemical coagulation. The optimal combination (EC-EO) treatment was established with Mp Ti-Bp Al, and it is found to be more active than EC alone. The optimal parameters of the EC process with a novel rotating anode were 4 mA/cm2 current density, 150 rpm rotational speed, and 10 minutes reaction time. EC process with a rotating anode was more active than model one and chemical coagulation, where the removal efficiency was higher, and the operational cost were reduced significantly. The increase of impellers anode diameter led toenhance the mass transfer coefficient of ionic aluminum. This result was confirmed by computational fluid dynamic (CFD) simulation results. By solar cell supply, the EC process with rotating anode reactor using batch and continuous flow regime had almost similar removal rate. Zeta potential tests showed that reaction was chemo-adsorption, and this was validated by the X-ray diffraction (XRD) analysis. Moreover, the reaction product was environmental friendly. Hydrogen production was improved at a rotation speed of anode. The electrode passivation was reduced by increasing rotational speed of anode which led to an improved in the EC process performance and validated the reactor design. Finally, the contribution of this study is a novel EC reactor with a rotating anode which is more efficient and economic as compared to the conventional coagulation process in the textile wastewater treatment.